2005
DOI: 10.1016/s0002-9440(10)62484-4
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Fusion of Circulating Fluorescent Cells with Dystrophin-Deficient Myofibers Results in Extensive Sarcoplasmic Fluorescence Expression but Limited Dystrophin Sarcolemmal Expression

Abstract: To investigate the therapeutic potential of bone marrow transplantation in Duchenne muscular dystrophy, green fluorescent protein-positive (GFP ؉ ) bone marrow cells were transplanted into irradiated wildtype and dystrophin-deficient mdx mice. Tibialis anterior muscles showed fivefold to sixfold more GFP ؉ mononucleated cells and threefold to fourfold more GFP ؉ myofibers in mdx than in wild-type mice. In contrast, dystrophin expression in mdx mice remained within the level of nontransplanted mdx mice, and co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 28 publications
4
28
0
2
Order By: Relevance
“…Six months after transplantation, TA muscle transections immunostained for basal lamina markers (laminin or collagen IV) showed a total number of 94 GFPϩ cells, 38 of which were sublaminal ( Figure 1D). Coimmunostaining showed nuclear Pax7 expression in a proportion of GFP-positive cells (n ϭ 7), as previously reported (Dreyfus et al, 2004;Chretien et al, 2005). Vascular proximity of these cells became obvious when collagen IV immunostaining was done as a supplementary reaction and merged with initial images of Pax7ϩ and GFPϩ cells (Figure 1, E-G).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Six months after transplantation, TA muscle transections immunostained for basal lamina markers (laminin or collagen IV) showed a total number of 94 GFPϩ cells, 38 of which were sublaminal ( Figure 1D). Coimmunostaining showed nuclear Pax7 expression in a proportion of GFP-positive cells (n ϭ 7), as previously reported (Dreyfus et al, 2004;Chretien et al, 2005). Vascular proximity of these cells became obvious when collagen IV immunostaining was done as a supplementary reaction and merged with initial images of Pax7ϩ and GFPϩ cells (Figure 1, E-G).…”
supporting
confidence: 83%
“…Although sublaminal SCs are derived mainly from somites (Gros et al, 2005), a small numbers of SCs may be generated from bone marrow grafts (LaBarge and Blau, 2002;Dreyfus et al, 2004). These ectopic SCs express canonic SC markers (Dreyfus et al, 2004;Chretien et al, 2005) but exhibit very limited myogenic potential once reisolated from muscle (Sherwood et al, 2004). Thus, they might represent foreign stem cells squatting in SC niches.…”
Section: Juxtavascular Niches Can Incorporate Bone Marrow-derived Cellsmentioning
confidence: 99%
“…The strategy is to deliver the protein missing from DMD muscle through the fusion of dystrophin-expressing myogenic cells with dystrophic myofibres. There is growing success in testing this modality of treatment (Chretien et al, 2005;Cossu and Mavilio, 2000;Cousins et al, 2004;Gussoni et al, 1999;Huard et al, 1994;Ikezawa et al, 2003;Jankowski and Huard, 2004;Li et al, 2005b;Liu et al, 2005;Partridge et al, 1989;Payne et al, 2005;Qu-Petersen et al, 2002).…”
Section: (2) Satellite Cells As a Conveyance In Skeletal Muscle Plastmentioning
confidence: 99%
“…could be more easily translated to therapy in patients. The first BMT in a dystrophic animal was performed in the mdx mouse, a model for DMD [28,29]. The authors found that some transplanted cells were able to engraft in the skeletal muscle, but not to express dystrophin.…”
mentioning
confidence: 99%